Selenium vacancy-containing Co < 0.85 > Se / Ni < 0.85 > Se heterojunction nano array electrode and preparation method and application thereof

Co0.85Se/Ni0.85Se heterojunction nanoarray electrode containing selenium vacancy was prepared by hydrothermal-plasma etching method, which solved the problem of insufficient activity and high cost of electrocatalyst in electrolytic hydrogen production, and achieved high activity and Stable electrocatalytic performance is better than precious metal catalysts.

CN119243229APending Publication Date: 2025-01-03XUZHOU NORMAL UNIVERSITY
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411252673.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-09
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

In the existing electrolytic hydrogen production technology, the electrocatalyst has high overpotential and slow kinetics, especially the oxygen evolution reaction (OER) catalyst has high cost and insufficient activity, which limits its application in the field of water electrolysis.

Method used

Co0.85Se/Ni0.85Se heterojunction nanoarray electrodes containing selenium vacancies were prepared by combining hydrothermal-plasma etching. By forming a hierarchical structure and heterogeneous interface, the electronic structure and active sites of the catalyst were adjusted. Improve electrocatalytic performance.

Benefits of technology

It significantly improves the activity and stability of the oxygen evolution reaction, is better than commercial precious metal catalysts, reduces the cost and reaction pressure of the electrocatalyst, and enhances the transfer efficiency of charge and ions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119243229A_ABST
    Figure CN119243229A_ABST
Patent Text Reader

Abstract

The invention relates to a Co < 0.85 > Se / Ni < 0.85 > Se heterojunction nano array electrode containing selenium vacancy as well as a preparation method and application of the Co < 0.85 > Se / Ni < 0.85 > Se heterojunction nano array electrode, and belongs to the field of electro-catalysis and new energy materials. The electrode material adopts a hydrothermal-plasma etching combined preparation method, and comprises the following steps: firstly, preparing a precursor Co (OH) F nanowire / Ni (OH) 2.7 H2O nanosheet composite nano array by adopting a hydrothermal reaction, then, carrying out selenylation treatment on the precursor through the hydrothermal reaction, and finally, carrying out plasma etching in an inert atmosphere to obtain the electrode material. And the Co < 0.85 > Se / Ni < 0.85 > Se heterojunction nano array electrode containing the selenium vacancy is obtained. By introducing selenium vacancy, the intrinsic activity of the catalyst is increased, and meanwhile, a stable heterojunction nano array structure is constructed, so that the oxygen evolution reaction performance of the electrode material is improved. The method has the advantages of simplicity and convenience in operation, low cost, suitability for industrial production and the like, and has a wide application prospect in the fields of water electrolysis and metal-air batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of electrocatalysis and new energy materials, and specifically relates to a Co-containing selenium vacancy 0.85 Se / Ni 0.85 Se heterojunction nanoarray electrode and its preparation method and application. Background Art

[0002] Due to the inevitable depletion of fossil fuels, people are increasingly concerned about environmental pollution and the global energy crisis, and the search for renewable and clean energy alternatives is urgent. Hydrogen energy has become an important alternative to traditional fossil resources due to its high energy density and clean, zero-pollution properties. Compared with traditional methane steam and coal gasification hydrogen production processes, water electrolysis is an effective green and carbon-free hydrogen production strategy, which has attracted much attention due to its mild conditions, environmental friendliness, and high product purity. However, the oxygen evolution reaction (OER) measured at the anode of the electrolyzer is slow in kinetics and has a high overpotential, resulting in a large water electrolysis voltage. Therefore, electrocatalysts are needed to accelerate the OER. Currently, the OER catalysts commonly used in industry are mainly Ru / Ir-based precious metal materials, but their high cost and low storage limit their large-scale application. Therefore, the design and development of highly active and stable non-precious metal electrocatalysts are of great significance.

[0003] In recent years, various studies have shown that nanoheterostructures formed by multiple components through specific interface contacts can regulate the electronic structure and performance of the catalyst surface. In addition, the introduction of defects / vacancies can accelerate the charge transfer of the catalyst or regulate the electronic structure of the transition metal active center, thereby optimizing the catalytic ability. For example, Wang et al. successfully constructed NiSe2 nanosheet arrays with selenium vacancies using plasma etching. The appearance of selenium vacancies not only activated more hydrogen evolution reaction (HER) active sites, but also reconstructed the local electronic structure and accelerated the charge transfer of the catalyst (ACS Applied Nano Materials, 2023, 6, 3848-3855); Zheng et al. synthesized NiSe2 / CoSe2 nanoheterostructures using a continuous ion implantation strategy, optimized the binding energy of oxygen-containing species, accelerated the reaction kinetics, and promoted the improvement of electrocatalytic performance (Advanced Materials, 2020, 32, 2000607). However, despite the remarkable results achieved in the above studies, transition metal selenides with a single structure are still limited by insufficient active sites and slow reaction kinetics, which seriously affects their application in the field of water electrolysis. Summary of the Invention

[0004] In order to solve the above problems, the present invention provides a Co-containing selenium vacancy based on interface and vacancy engineering. 0.85 Se / Ni0.85 Se heterojunction nanoarray electrode. The electrode material of the present invention is prepared by a hydrothermal-plasma etching method, which includes first using a hydrothermal reaction to prepare a precursor Co(OH)F nanowire / Ni(OH)2·7H2O nanosheet composite nanoarray, then selenizing the precursor through a hydrothermal reaction, and finally plasma etching under an inert atmosphere to obtain a Co(OH)F nanowire / Ni(OH)2·7H2O nanosheet composite nanoarray. 0.85 Se / Ni 0.85 Se heterojunction nanoarray electrode.

[0005] The technical solutions adopted in the present invention are as follows:

[0006] (1) dissolving metal (cobalt, nickel) salt, ammonium fluoride, and urea in deionized water to obtain a mixed aqueous solution;

[0007] (2) immersing the substrate material in the mixed solution prepared above, and performing a hydrothermal reaction at a specific temperature for a certain time, washing after cooling, and drying to obtain a Co(OH)F nanowire / Ni(OH)2·7H2O nanosheet precursor;

[0008] (3) Dissolve the raw material Se powder and sodium borohydride in deionized water to obtain a clear NaHSe aqueous solution. Soak the precursor material in step (2) in the NaHSe aqueous solution, perform hydrothermal treatment again, cool, wash, and dry to obtain Co 0.85 Se / Ni 0.85 Se heterojunction nanoarray electrode;

[0009] (4) The above-mentioned electrode is placed in a plasma-enhanced tube furnace, and etched and maintained for a certain time under an inert atmosphere and a specific temperature to obtain Co containing selenium vacancies. 0.85 Se / Ni 0.85 Se heterojunction nanoarray electrode.

[0010] Wherein, in step (1), the metal salt includes but is not limited to nitrate, chloride and sulfate; the molar ratio of the metal salt, ammonium fluoride and urea is (1-6):(6-10):(1-6).

[0011] Wherein, in step (2), the substrate material includes but is not limited to nickel foam, copper foam, nickel mesh, copper mesh, iron mesh, carbon cloth, carbon paper, etc.

[0012] Wherein, in step (2), the hydrothermal reaction temperature is 100-200° C., and the reaction time is 5-24 h.

[0013] Wherein, in step (3), the concentration of NaHSe aqueous solution is 0.5~3 mol L -1 ; The hydrothermal reaction temperature is 100-200°C, and the reaction time is 5-24h.

[0014] Wherein, in step (4), the inert atmosphere includes argon and helium, the etching temperature is 25-600° C., the etching power is 150-250 W, and the etching time is 5-60 min.

[0015] Another aspect of the present invention provides Co containing selenium vacancies obtained by the above preparation method 0.85 Se / Ni 0.85 Se heterojunction nanoarray electrode for oxygen evolution reaction electrocatalyst.

[0016] The present invention has the following beneficial effects compared to the prior art:

[0017] (1) The self-supporting electrode of the present invention has a hierarchical structure and a large specific surface area, which can increase the contact area between the electrolyte solution and the electrocatalyst, thereby promoting the transfer of charges and the rapid transfer of ions / electrons during the electrochemical reaction.

[0018] (2) The formation of heterogeneous interfaces in the material helps to regulate the electronic structure and performance of the catalyst surface. At the same time, the introduction of selenium vacancies can not only reconstruct the local electronic structure, but also increase the active sites of the catalyst and improve the electrocatalytic activity of the catalyst.

[0019] (3) Co containing selenium vacancies according to the present invention 0.85 Se / Ni 0.85 The Se heterojunction nanoarray electrode exhibits superior OER activity / stability to commercial noble metal catalysts under alkaline conditions. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] In order to more clearly illustrate the embodiments of the present invention, the drawings related to the embodiments are briefly introduced below.

[0021] Figure 1 The XRD patterns of the samples prepared in Comparative Example 1, Comparative Example 2 and Example 1 are shown.

[0022] Figure 2 These are SEM images of the samples prepared in Comparative Example 1, Comparative Example 2 and Example 1.

[0023] Figure 3 LSV curves of the OER performance of the samples prepared in Comparative Example 1, Comparative Example 2 and Example 1 in N2-saturated 1M KOH electrolyte.

[0024] Figure 4 The Tafel plots of the samples prepared in Comparative Example 1, Comparative Example 2 and Example 1 are shown.

[0025] Figure 5 This is a CV comparison chart of the sample prepared in Example 1 before and after stability. DETAILED DESCRIPTION

[0026] The present invention is described in detail below with reference to the embodiments, but the embodiments of the present invention are not limited thereto. Obviously, the embodiments described below are only some embodiments of the present invention. For those skilled in the art, other similar embodiments obtained without creative work all fall within the scope of protection of the present invention.

[0027] The nickel foam substrates used in the examples were pretreated as follows: 1×4 cm nickel foam was cleaned in deionized water, acetone, deionized water, hydrochloric acid, and deionized water ultrasonically for 15 min, placed in a 60° C. vacuum drying oven, and dried for 2 h for use.

[0028] Comparative Example 1:

[0029] Ni foam based on Ni 0.85 Preparation of Se / NF electrocatalyst:

[0030] (1) Weigh 1 mmol Ni(NO3)2·6H2O, 2 mmol NH4F, and 5 mmol (NH2)2CO in a beaker, add 35 mL of deionized water, stir magnetically for 30 min, and ultrasonicate for 10 min.

[0031] (2) The mixed solution prepared above was poured into a 50 mL polytetrafluoroethylene reactor, and the treated nickel foam was placed vertically in a 120°C forced air drying oven for hydrothermal reaction for 6 h. After the sample was cooled, it was washed several times and vacuum dried at 60°C for 2 h to obtain Ni(OH)2·7H2O / NF.

[0032] (3) 30 mL of deionized water was added to a 50 mL polytetrafluoroethylene reactor. Under the action of N2, 12 mmol of NaBH4 and 4 mmol of Se powder were added in sequence to prepare a NaSeH mixed solution. Ni(OH)2·7H2O / NF was then placed vertically in a blast drying oven at 120°C for hydrothermal reaction for 6 h. After the sample was cooled, it was washed and vacuum dried at 60°C for 2 h to obtain Ni 0.85 Se / NF electrocatalyst.

[0033] Comparative Example 2:

[0034] Co based on nickel foam 0.85 Se / Ni 0.85 Preparation of Se / NF electrocatalyst:

[0035] (1) Weigh 1 mmol Co(NO3)2·6H2O, 1 mmol Ni(NO3)2·6H2O, 2 mmol NH4F, and 5 mmol (NH2)2CO into a beaker, add 35 mL of deionized water, stir magnetically for 30 min, and ultrasonicate for 10 min.

[0036] (2) The mixed solution prepared above was poured into a 50 mL polytetrafluoroethylene reactor, and the treated nickel foam was placed vertically in a 120°C forced air drying oven for hydrothermal reaction for 6 h. After the sample was cooled, it was washed several times and vacuum dried at 60°C for 2 h to obtain Co(OH)F / Ni(OH)2·7H2O.

[0037] (3) 30 mL of deionized water was added to a 50 mL polytetrafluoroethylene reactor. Under the action of N2, 12 mmol of NaBH4 and 4 mmol of Se powder were added in sequence to prepare a NaSeH mixed solution. Co(OH)F / Ni(OH)2·7H2O was then placed vertically in a blast drying oven at 120°C for hydrothermal reaction for 6 h. After the sample was cooled, it was washed and vacuum dried at 60°C for 2 h to obtain Co 0.85 Se / Ni 0.85 Se / NF electrocatalyst.

[0038] Example 1:

[0039] Nickel foam-based V se -Co 0.85 Se / Ni 0.85 Preparation of Se / NF electrocatalyst:

[0040] (1) Weigh 1 mmol Co(NO3)2·6H2O, 1 mmol Ni(NO3)2·6H2O, 2 mmol NH4F, and 5 mmol (NH2)2CO into a beaker, add 35 mL of deionized water, stir magnetically for 30 min, and ultrasonicate for 10 min.

[0041] (2) The mixed solution prepared above was poured into a 50 mL polytetrafluoroethylene reactor, and the treated nickel foam was placed vertically in a 120°C forced air drying oven for hydrothermal reaction for 6 h. After the sample was cooled, it was washed several times and vacuum dried at 60°C for 2 h to obtain Co(OH)F / Ni(OH)2·7H2O.

[0042] (3) 30 mL of deionized water was added to a 50 mL polytetrafluoroethylene reactor. Under the action of N2, 12 mmol of NaBH4 and 4 mmol of Se powder were added in sequence to prepare a NaSeH mixed solution. Co(OH)F / Ni(OH)2·7H2O was then placed vertically in a blast drying oven at 120°C for hydrothermal reaction for 6 h. After the sample cooled, it was washed and vacuum dried at 60°C for 2 h. It was transferred to Ar plasma and etched at 200 W for 10 min. After cooling to room temperature, V was obtained. se -Co 0.85 Se / Ni 0.85 Se / NF electrocatalyst.

[0043] Figure 1 The XRD patterns of the samples prepared in Comparative Example 1, Comparative Example 2 and Example 1 are shown; in order to determine the structure and composition of the catalyst, Figure 1 As shown, the diffraction peaks are located at 33.20°, 50.51°, 61.81°, 69.87°, 71.34°, 82.16°, and 83.71°, respectively, corresponding to Ni 0.85 The diffraction peaks of (101), (110), (201), (202), (004), (203), and (211) planes of Se (JCPDS no. 018-0888) are located at 33.20°, 50.51°, 61.89°, 69.87°, and 71.34°, respectively, corresponding to Co 0.85 Se (JCPDS no. 052-1008) (101), (110), (112), (202), (004) planes. 0.85 Se / Ni 0.85 From the heterogeneous structure of Se, it can be observed that the diffraction peak comes from Co 0.85 Se and Ni 0.85 The diffraction of similar crystal planes of Se overlaps, and the Ni 0.85 Compared with the single peak of Se, the diffraction peak shifted, and the diffraction peak of comparative example 2 became significantly broadened, indicating that the particles of the electrocatalyst were smaller, which may be due to the 0.85 Se and Ni 0.85 Se heterojunction is related to the electronic interaction between the interfaces. In order to obtain better results, the Co 0.85 Se / Ni 0.85 Se / NF was further etched with Ar plasma to generate selenium vacancies. Its XRD diffraction peaks were found to be similar to those in Comparative Example 2, and no additional diffraction peaks appeared, proving that no new phase was formed in the sample after plasma etching.

[0044] Figure 2The SEM images of the samples prepared in Comparative Example 1, Comparative Example 2 and Example 1 are shown in FIG. 1 . As can be seen from the figure, the morphology of Comparative Example 1 (a) is mainly composed of the synthesized Ni 0.85 Se nanosheets are the main ones; the morphology of comparative example 2 (b) is mainly Ni 0.85 Se nanosheets and Co 0.85 Se nanowires are the main materials. It can be observed that due to the addition of cobalt source, a distinct heterogeneous interface between nanosheets and nanowires is constructed. This structure can expose active catalytic sites and is also conducive to the mutual transfer between electrons. The morphology of Example 1(c) is similar to that of Comparative Example 2(b), indicating that under the action of Ar plasma etching, V se -Co 0.85 Se / Ni 0.85 The surface of Se / NF nanosheets and wires is rougher, and a certain amount of selenium vacancies are also generated. This special structure can produce more active sites, thereby effectively improving the electrocatalytic activity of the catalyst.

[0045] Figure 3 The OER performance LSV curves of the samples prepared in Comparative Example 1, Comparative Example 2 and Example 1 in N2 saturated 1M KOH electrolyte. As can be seen from the figure, Example 1 has the best OER performance, and its 100mA cm -2 The corresponding voltage is the minimum (1.56V).

[0046] Figure 4 The Tafel plots of the samples prepared in Comparative Example 1, Comparative Example 2 and Example 1 are shown in FIG. 1 . As shown in the figure, Example 1 has a smaller Tafel slope (21.5 mV dec) than Comparative Example 1 and Comparative Example 2. -1 ), which is more prone to electrochemical reaction and has a faster OER kinetic process.

[0047] Figure 5 This is a CV comparison diagram of the sample prepared in Example 1 before and after stability. It can be seen from the figure that the LSV curve before and after 86h only differs by 10mV, indicating that the catalyst has relatively stable OER catalytic performance under alkaline conditions.

[0048] It should be noted that the above embodiments are only for further illustrating the present invention and should not be construed as limiting the present invention. Without departing from the spirit and substance of the present invention, modifications or replacements made to the methods, steps or conditions of the present invention are within the scope of the present invention.

Claims

1. A Co with Se vacancy 0.85 Se / Ni 0.85 Se heterojunction nanoarray electrode, characterized by: The Co 0.85 Se / Ni 0.85 The Se self-supporting electrode is a nanoarray with a hierarchical structure formed by interlacing nanowires and nanosheets.

2. A Co with Se vacancy 0.85 Se / Ni 0.85 Se heterojunction nanoarray electrode, characterized by: The Co 0.85 Se / Ni 0.85 Se free-standing electrodes are rich in Se vacancies.

3. Preparation of a Co containing selenium vacancies as described in claims 1 and 2 0.85 Se / Ni 0.85 Se heterojunction nanoarray electrode method, characterized in that The steps include: S1: dissolving metal (cobalt, nickel) salt, ammonium fluoride and urea in deionized water to obtain a mixed aqueous solution; S2: soaking the substrate material in the mixed solution prepared in S1, and hydrothermally reacting it at a specific temperature for a certain period of time, washing it after cooling, and drying it to obtain a Co(OH)F nanowire / Ni(OH)2·7H2O nanosheet precursor; S3: Dissolve the raw material Se powder and sodium borohydride in deionized water to obtain a clear NaHSe aqueous solution. Soak the precursor material described in S2 in the NaHSe aqueous solution, perform hydrothermal treatment again, and after cooling, wash and dry to obtain Co 0.85 Se / Ni 0.85 Se heterojunction nanoarray electrode; S4: Place the electrode described in S3 in a plasma-enhanced tube furnace, etch and maintain for a certain time under an inert atmosphere and a specific temperature to obtain Co containing selenium vacancies. 0.85 Se / Ni 0.85 Se heterojunction nanoarray electrode.

4. The preparation method according to claim 3, characterized in that: In step S1, the metal salt includes but is not limited to nitrate, chloride and sulfate; the molar ratio of the metal salt, ammonium fluoride and urea is (1-6):(6-10):(1-6).

5. The preparation method according to claim 3, characterized in that: In step S2, the substrate material includes but is not limited to foam nickel, foam copper, nickel mesh, copper mesh, iron mesh, carbon cloth, carbon paper, etc.

6. The preparation method according to claim 3, characterized in that: In step S2, the hydrothermal reaction temperature is 100-200° C., and the reaction time is 5-24 hours.

7. The preparation method according to claim 3, characterized in that: In step S3, the concentration of the NaHSe aqueous solution is 0.5 to 3 mol L -1 ; The hydrothermal reaction temperature is 100-200°C, and the reaction time is 5-24h.

8. The preparation method according to claim 3, characterized in that: In step S4, the inert atmosphere includes argon and helium, the etching temperature is 25-600° C., the etching power is 150-250 W, and the etching time is 5-60 min.

9. Co containing selenium vacancies obtained by the preparation method according to any one of claims 3 to 8 0.85 Se / Ni 0.85 Se heterojunction nanoarray electrode.

10. The Co containing selenium vacancies according to claim 9 0.85 Se / Ni 0.85 Application of Se heterojunction nanoarray electrodes in water electrolysis and / or metal-air batteries.

Citation Information

Cited By

  • Composite nano array material with Se vacancy, electrode, supercapacitor and preparation method thereof

    CN119517629A